2022
DOI: 10.1111/jipb.13329
|View full text |Cite
|
Sign up to set email alerts
|

SICKLE represses photomorphogenic development of Arabidopsis seedlings via HY5‐ and PIF4‐mediated signaling

Abstract: Arabidopsis CONSTITUTIVELY PHOTOMORPHO GENIC1 (COP1) and PHYTOCHROME INTER-ACTING FACTORs (PIFs) are negative regulators, and ELONGATED HYPOCOTYL5 (HY5) is a positive regulator of seedling photomorphogenic development. Here, we report that SICKLE (SIC), a proline rich protein, acts as a novel negative regulator of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Plants have evolved a complex but sophisticated regulatory mechanism to fine-tune the activity of HY5 in regulating photomorphogenesis ( 15 , 52 ). BBXs play key roles in modulating the activity of HY5 by acting as transcriptional cofactors or inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Plants have evolved a complex but sophisticated regulatory mechanism to fine-tune the activity of HY5 in regulating photomorphogenesis ( 15 , 52 ). BBXs play key roles in modulating the activity of HY5 by acting as transcriptional cofactors or inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factor PIF4 was initially characterized as a key component of phytochrome‐ and auxin‐signaling pathways (Lau and Deng, 2010; Zhao and Bao, 2021), which served in several biological processes, including young seedling hypocotyl elongation (Gao et al, 2022; Lan et al, 2022), plant thermomorphogenesis, heat response and leaf senescence (Li et al, 2021; Lee et al, 2021b), as well as in response to several phytohormones and diverse environmental cues (Choi and Oh, 2016; Huang et al, 2019; Yan et al, 2020b; Qiu et al, 2021; Xu and Zhu, 2021; Li et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that PIF6 might be a regulator for seed dormancy as a result of alternative splicing (Penfield et al, 2010), although the detailed molecular mechanisms underlying this process are still unclear. PIF4 is a master protein involved in seedling hypocotyl elongation (Huang et al, 2015; Ma et al, 2016; Li et al, 2020), plant shade signaling (Luo et al, 2022), plant thermomorphogenesis (Lee et al, 2021b) and response to several hormones and environmental cues (Choi and Oh, 2016; Yan et al, 2020b; Xu and Zhu, 2021; Li et al, 2022). However, whether and, if so, how the PIF4‐mediated complex is involved in seed dormancy control remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive amount of the constructed pCAMBIA1302- TaPsb28 was transformed into wild-type Arabidopsis thaliana (Columbia-0) by the floral dip method [ 49 , 50 ]. Transgenic overexpression lines were selected on MS medium containing 25 mg/L hygromycin supplementation, 2-week-old green seedlings of the T 2 generation were confirmed by PCR and the product was validated by sequencing.…”
Section: Methodsmentioning
confidence: 99%